ANALISIS HUKUM PERAN PENGAWASAN SYAHBANDAR DALAM PENGIRIMAN BARANG DI PELABUHAN NUSANTARA PAREPARE - Sadriyah Mansur, Nurhaedah Hasan, Irma Reisasari (Madani Legal Review, 2023)
Delivery of goods is very necessary to meet socio-economic needs, therefore supervision is needed by the port management unit to oversee every shipment of goods that occurs so that illegal shipments of goods do not occur. The research with the title "Legal analysis of the supervisory role of the syahbnadar in the delivery of goods at the Nusantara port of Parepare", has the formulation of the problem how to analyze the legal role of the syahbnadar supervisory role in the process of shipping goods at the Nusantara port of Parepare city. And what are the obstacles to the harbor master in the process of supervising the delivery of goods at the Nusantara port, Parepare city. The purpose of this research is to find out the legal analysis of the supervisory role of the syahbnadar in the delivery of goods at the Nusantara port in Parepare, and also to find out the obstacles that the syahbnadar often encounters in the process of supervising the delivery of goods at the Nusantara Parepare port. This research uses a descriptive-qualitative research type with an empirical normative approach while the data collection technique used is by means of literature studies, field studies and interviews. Based on Law No. 17 of 2008 concerning shipping, it is the basis that almost all activities in the port are part of the syahbandar's responsibilities as the highest authority.